Effect of Betaine Supplementation on Serum Metabolite Profile in Gestating Sows - Mishra, Alok; Verma, A K; Das, Asit; Singh, Putan; Sahoo, N R (Indian Journal of Animal Nutrition, 2019)
Present study was conducted to investigate the effect of betaine supplementation on serum metabolite profile in gestating sows. For the study, eighteen crossbred (Landrace X Desi) inseminated sows were randomly distributed into three treatment groups with six sows per treatment in completely randomized design. T0 (control) group was supplemented with basal diet, whereas, T1 and T2 treatment groups were fed basal diet supplemented with betaine @ 3g/kg dry matter during late gestation (76 days before to farrowing) and throughout the length of gestation, respectively. There were no significant (P>0.05) differences in serum glucose, albumin, globulin, total protein, albumin/globulin ratio and creatinine levels among the groups. whereas, serum cholesterol and triglyceride levels were significantly (P<0.05) lower in T2 group as compared to T0 and T1Â groups..Thus, it can be concluded that, dietary betaine supplementation @ 3 g/kg throughout the length of gestation was helpful in decreasing the serum cholesterol and triglyceride levels in sows